2022
DOI: 10.1093/cid/ciac648
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Influenza in Managed Quarantine in Australia and the Estimated Risk of Importation

Abstract: Background Influenza circulated at historically-low levels during 2020 and 2021 due to COVID-19 pandemic travel restrictions. In Australia, international arrivals to Australia were required to undertake 14 days hotel quarantine to limit new introduction of SARS-CoV-2 virus. Methods We used routine testing data for travellers arriving on repatriation flights to Darwin, Australia from 3 January to 11 October 2021 to identify im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Of the remaining 587 articles, 547 were discarded for not matching the inclusion criteria (of these, 62 were not further considered since no reported influenza cases were type B), 7 for being based on the WHO FluNet and/or GISAID database, 3 for being previous reports from the GIHSN, and 4 because of overlap with more recent and/or larger articles based on the same data sources. A total of 26 articles were included in the systematic review: their main characteristics are reported in Table 1 [ Soldevila 2022, Murillo-Zamora 2021, Korsun 2021, Panatto 2021, Pablo-Marcos 2020, Miron 2021, Hu 2021, Omer 2022, Olson 2022, Auvinen 2022, Kuzmanovska 2021, Wagatsuma 2022, Heinzinger 2021, Rios-Silva 2022, Suntronwong 2021, da Costa 2022, Melidou 2020, Huang 2022, O’Neill 2022, Kolosova 2022, Peck 2023, Chon 2023, Merced-Morales 2022, Melidou 2022, Sominina 2022, Song 2022 ]. Europe was the most represented area (12 articles, of which 2 reported findings from multiple countries in the WHO European Region), followed by Asia (n=6), North America (n=5), and Oceania and South America (n=1 each).…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 587 articles, 547 were discarded for not matching the inclusion criteria (of these, 62 were not further considered since no reported influenza cases were type B), 7 for being based on the WHO FluNet and/or GISAID database, 3 for being previous reports from the GIHSN, and 4 because of overlap with more recent and/or larger articles based on the same data sources. A total of 26 articles were included in the systematic review: their main characteristics are reported in Table 1 [ Soldevila 2022, Murillo-Zamora 2021, Korsun 2021, Panatto 2021, Pablo-Marcos 2020, Miron 2021, Hu 2021, Omer 2022, Olson 2022, Auvinen 2022, Kuzmanovska 2021, Wagatsuma 2022, Heinzinger 2021, Rios-Silva 2022, Suntronwong 2021, da Costa 2022, Melidou 2020, Huang 2022, O’Neill 2022, Kolosova 2022, Peck 2023, Chon 2023, Merced-Morales 2022, Melidou 2022, Sominina 2022, Song 2022 ]. Europe was the most represented area (12 articles, of which 2 reported findings from multiple countries in the WHO European Region), followed by Asia (n=6), North America (n=5), and Oceania and South America (n=1 each).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a 14-day mandatory quarantine for returning Australian residents in supervised facilities (principally hotels) was introduced on 28 March 2020 [7]. Initiation of travel restrictions coincided with a dramatic reduction in influenza in Australia [8]. Only 33 of 60,031 specimens tested in Australia were positive for influenza between April and July 2020 [3], and between April 2020 and October 2021, confirmed cases were largely confined to quarantined travellers [8].…”
Section: Introductionmentioning
confidence: 99%
“…There was also a global lack of influenza B/Yamagata identification in 2021 [8,9]. Nevertheless, sporadic cases of influenza infection have been reported [10], especially in tropical regions of Asia and West Africa [11,12 ▪ ]. With a gradual relaxation of NPI and the resumption of international travel in the year 2022 to 2023, seasonal influenza is expected to return [13].…”
Section: Introductionmentioning
confidence: 99%